Parâmetros de irrigação por análise numérica para a cultura do milho na região central do Rio Grande do Sul - Trentin, Gustavo (2009)
Maize is a main crop in Brazil. Maize yield can be decreased by water deficit. Irrigation is an alternative to overcome this problem and avoid the low soil water availability. In order to efficiently irrigate a crop it is necessary to know some parameters and irrigation and crop requirements in each region. The objective of this study was to determine the most likely values the duration of developmental phases, water depth and the number of irrigations required for maize crop sown at different sowing dates, considering the water storage capacity of main soils of the Central Area of Rio Grande do Sul State and its variation with simulated developmental stage. Crop development for three maturation groups was simulated using the thermal time, for 14 sowing dates, from August until mid-February, every during the period from 1968 to 2008, covered by metereorological data at Santa Maria RS (EMPSM). To 13 soils, were grouped into six groups with similar water storage capacity (CAD) and infiltration capacity. Daily water balance was calculated when soil reached a minimum fraction of available water, according to four management levels (water withdrawn from the soil reached 20%, 30%, 40% and 50% of CAD). Data analysis consisted of analysis of variance, mean comparison tests and probability distribution analysis of the duration of crop developmental phases and the entire developmental cycle, water depth and number of irrigations. Developmental until tasseling are larger in the earliest sowing date (01/08). After tasseling, the greater duration of developmental phases occurs in the latest sowing (15/02). The normal and lognormal distributions represent better the variation of the duration of maize development both for the duration of the phases and the entire cycle. Sowing dates from early October to early November result a greater need water depth considering the entire cycle, regardless of the soil and maturation group. The mid maturation group needs more water during the entire cycle for all sowing dates, and the very early maturation group has the lowest water requirement. The variation of water depth and the number of irrigations follow the normal, lognormal, gamma and Weibull probability distribution functions. For the 90% probability level the water depth varies between 31 and 171 mm and the number of irrigations varies between one and nineteen during the developmental cycle, depending on sowing date, maize maturation group and soil.